Current Mode Full-Wave Rectifier Based on a Single MZC-CDTA - Neeta Pandey; Rajeshwari Pandey (Active and Passive Electronic Components)
This paper presents a current mode full-wave rectifier based on single modified Z copy current difference transconductance amplifier (MZC-CDTA) and two switches. The circuit is simple and is suitable for IC implementation. The functionality of the circuit is verified with SPICE simulation using 0.35 μm TSMC CMOS technology parameters.